Specific types of femoral head fractures: be alert for pre‐, intra‐, and post‐operative ipsilateral femoral neck fractures following fracture‐dislocation of the femoral head - Shenghui Wu; Jiong Mei (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose Ipsilateral femoral head and neck fractures (iFHNFs) are rare types of fractures that confer extremely poor prognosis among femoral head fractures (FHFs). Owing to the rarity of FHFs, it is challenging to diagnose iFHNFs. In addition, the clinical features of iFHNF have not yet been comprehensively elucidated. Therefore, this retrospective study aimed to summarize and analyze the clinical characteristics of iFHNF using a clinical diagnostic simulation based on a prospectively maintained database. Methods Clinical data of consecutive patients with FHFs, including gender, age, injury side, and associated injuries, were collected and analyzed from a prospectively maintained orthopedic database at a large level‐I trauma center for a clinical diagnostic simulation. Patients were stratified according to the presence or absence of iFHNF. Moreover, propensity score matching (PSM) was used to create 1:1 age‐ and gender‐matched couples. Lastly, clinical factors were compared and identified between the two groups before and after matching. Results A total of 218 FHF patients were included. Fifteen patients were diagnosed with ipsilateral femoral neck fractures (iFNFs), including preoperative, intraoperative, and postoperative types. There were 177 male and 41 female patients, with a mean age of 40.0 ± 16.5 years. The incidence of two factors, namely acetabular fracture and posterior hip dislocation, were significantly different between the two groups (P < 0.05). Following PSM, 15 pairs of patients were generated. Comparisons revealed that the incidence of posterior hip dislocation was significantly different between the two groups (P < 0.05). Conclusions There were three types of iFHNFs. In the context of FHFs, posterior hip dislocation was associated with iFNFs. Thus, surgeons should remain vigilant, not only intraoperatively but also postoperatively, for iFNFs following FHF and concomitant posterior hip dislocation. Level of Evidence Diagnostic level IV